2022
DOI: 10.3390/jof8101110
|View full text |Cite
|
Sign up to set email alerts
|

Roles of BrlA and AbaA in Mediating Asexual and Insect Pathogenic Lifecycles of Metarhizium robertsii

Abstract: BrlA and AbaA are key activators of the central developmental pathway (CDP) that controls asexual development in Aspergillus but their roles remain insufficiently understood in hypocerealean insect pathogens. Here, regulatory roles of BrlA and AbaA orthologs in Metarhizium robertsii (Clavicipitaceae) were characterized for comparison to those elucidated previously in Beauveria bassiana (Cordycipitaceae) at phenotypic and transcriptomic levels. Time-course transcription profiles of brlA, abaA, and the other CDP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Recent studies have confirmed that brlA and abaA regulate asexual development in B. bassiana ( 20 ) and M. robertsii ( 34 ), as they do in A. nidulans . The regulated processes include aerial conidiation and submerged blastospore production mimicking proliferation in vivo after hyphal invasion into insect hemocoel.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Recent studies have confirmed that brlA and abaA regulate asexual development in B. bassiana ( 20 ) and M. robertsii ( 34 ), as they do in A. nidulans . The regulated processes include aerial conidiation and submerged blastospore production mimicking proliferation in vivo after hyphal invasion into insect hemocoel.…”
Section: Introductionmentioning
confidence: 71%
“…The Δ wetA transcriptome was then compared with the Δ brlA and Δ abaA transcriptomes (up/down ratios: 52:203 and 101:122, respectively), analyzed previously in M. robertsii ( 34 ). Surprisingly, the 3 transcriptomes comprised 64 co-dysregulated genes, including 44 co-downregulated, 8 co-upregulated, and 12 differentially regulated ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In F. graminearum , FgSec22 was reported to be indispensable for normal conidiation and conidial morphology [ 24 ]. In the present study, the reduced conidiation level correlated with transcriptional repression of several asexual development-required genes, particularly brlA , abaA , and wetA , crucial for the conidiation of Beauveria bassiana , Monascus ruber , and other fungi [ 52 , 53 , 54 ]. In B. bassiana , loss-of-function mutations of wetA have compromised conidiation capacity by 98% [ 55 ].…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, BrlA and AbaA are highly conserved activators of asexual development in filamentous fungi [ 56 , 57 ]. BrlA and AbaA are indispensable for aerial conidiation in Metarhizium roberstii as well as in B. bassiana [ 52 , 54 ]. These results indicate that Sec22 plays a conserved role in sustaining mycelial radial growth, aerial hyphal development, and conidiation in filamentous fungi, and is also crucial for the development of the hyphal septation and nuclear division in A. oligospora .…”
Section: Discussionmentioning
confidence: 99%